2016
DOI: 10.1002/mus.25266
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐ganglioside antibodies in Guillain–Barré syndrome and chronic inflammatory demyelinating polyneuropathy in Chinese patients

Abstract: These results suggest that IgG anti-GM1 antibodies are associated with AMAN, but not with AIDP, and that IgM antibodies against GM1, GM2, and GM3 are associated with facial nerve palsy. Muscle Nerve 55: 470-475, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
4
21
1
1
Order By: Relevance
“…When compared with AMAN, antiganglioside antibodies are not found to be associated with AIDP. 29 Antibodies to moesin, which take part in myelination, was found in patients who developed AIDP after CMV infections. On the other hand, antibodies to neurofascin were found to be shared by central/peripheral nervous system demyelinating disorders.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…When compared with AMAN, antiganglioside antibodies are not found to be associated with AIDP. 29 Antibodies to moesin, which take part in myelination, was found in patients who developed AIDP after CMV infections. On the other hand, antibodies to neurofascin were found to be shared by central/peripheral nervous system demyelinating disorders.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…However, Fan et al. (2017) suggested that facial nerve palsy was connected to the presence of IgM‐AGA. Only 48.3% (14/29) of patients have symptoms of a respiratory or gastrointestinal tract infection before the onset of GBS which was found in our articles, <two‐thirds described by van den Berg et al.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, IgM or IgG antibody to GM1 were detected in 0–17% or 0–23% of patients with CIDP using enzyme‐linked immunosorbent assay (ELISA) or thin layer chromatography (TLC) . In addition, recent research reports that 27.8% (5/18) or 5.6% (1/18) of patients with CIDP comprised IgM or IgG anti‐GM1 antibody . Antecedent infections are rarely observed in CIDP patients.…”
Section: Glycolipid Antibodies In Chronic Inflammatory Demyelinating mentioning
confidence: 99%
“…[56][57][58][59][60] In addition, recent research reports that 27.8% (5/18) or 5.6% (1/18) of patients with CIDP comprised IgM or IgG anti-GM1 antibody. 61 Antecedent infections are rarely observed in CIDP patients. However, Mel endez-V asquez et al reported serological evidence of C. jejuni in 10% (4/ 40) of patients with CIDP.…”
Section: Gm1 Antibodymentioning
confidence: 99%